ANALYSIS & DESIGN OF INTEGRATED DOUBLE BUCK BOOST CONVERTER FOR POWER LED LAMPS - Sheena .T, Dr. Sreedevi .V.T (International Journal of Research Science and Management, 2015)
In this paper, an integrated double buck boost converter which act as a LED driver is presented. Here a 70 W IDBB converter is analyzed and designed which is fed from a 230 V/ 50 Hz ac supply and is used mainly for street lighting.